Ecological value of gravel pit ponds for floodplain wetland fish. (12th December 2022) - Nakahashi, Honoka; Yamada, Taihei; Ishiyama, Nobuo; Nakamura, Futoshi
Abstract: Floodplain wetlands support high biodiversity, but they have been degraded and geographically fragmented due to human activities. Some types of human‐created waterbodies have received growing attention as alternative habitats for conserving wetland biodiversity. Gravel pit ponds (GPPs) are human‐created wetlands formed when a gravel pit is excavated at or below the water table and filled with groundwater. Differences in community structure among GPPs and floodplain wetlands with respect to habitat characteristics are scarcely known, resulting in insufficient evaluations of the ecological value of GPPs for floodplain wetland species. In this study, we evaluated the ecological value of GPPs for wetland fishes in floodplain landscapes. We surveyed fish abundance, community composition, and 10 environmental factors in GPPs and two types of floodplain ponds (remnant ponds and river backwaters) to clarify the biotic and abiotic differences among the pond types. Environmental factors were similar among the pond types, with only water temperature and the distance from the main channel to the pond significantly lower in river backwaters. The richness and abundance of native fish species did not differ among the pond types, but species composition did. Rhynchocypris percnura sachalinensis, Carassius sp., and Lethenteron sp. N (one of the two cryptic species of Lethenteron reissneri ) were selected as indicator species in GPPs, remnant ponds, and river backwaters, respectively. These results indicate that GPPs provide valuable habitats for wetland fishes in floodplain landscapes and support regional γ diversity. Since many species inhabited the GPPs in this study, including red list species, appropriate management of GPPs is important to conserve wetland fishes.